Utilization of Boiler Ash as Growing Media and Vermicompost on Onion (Allium ascalonicum L.) Growth and Yield - denny febriyanto; Anis Rosyidah; Siti Muslikah; Nurhidayati Nurhidayati (AGRONISMA, 2022)
Consumption of onion in Indonesia continues to increase from year to year. This is due to the large number of processed industries from these commodities. But on the other hand, the conversion of productive land into non-agricultural land is increasingly widespread. Therefore, it is necessary to have an alternative onion cultivation system using soilless planting media to maintain onion production. This study aimed to determine the interaction between the proportion of growing media containing boiler ash and vermicompost on the growth and yield of onion (Allium ascolonicum L.). The design used is a factorial Randomized Block Design (RBD) which consists of two factors. The first factor was the proportion of growing media which consists of three levels, namely: M1 = Cocopeat 900 g +Boiler Ash 450 g + Sand 900 g, M2 = Cocopeat 900 g + Boiler Ash 900 g + Sand 450 g, M3 = Cocopeat 750 g + Boiler Ash 750 g + Sand 750 g. The second factor 2 is the dose of vermicompost, consisting of three levels (200, 400, 600 g pot-1). The results of this study indicated that there was a significant interaction effect between the proportion of growing media and the dose of vermicompost on the growth of leaf area and the total dry weight yield of onion plant. In general, the proportion of M1 and M2 growing media gave the same growth rate. Meanwhile, the difference in vermicompost doses gave the growth and yield of onion which were not significantly different. These results also indicate that the use of a low dose of 200 g pot-1 is more efficient than the higher dose.